Ketepatan Sasaran Anggaran dan Akuntabilitas Kinerja Instansi Pemerintah - Teguh Erawati; Hildegardis Olci Herawati (Universitas Muhammadiyah Metro, 2025)
This study aims to prove the effect of the dimensions of accountability, accuracy of budget targets and implementation of performance-based budgeting on performance accountability of government agencies. The sampling technique uses the pemprov sampling method. The population in this study were all employees in the Yogyakarta City Procurement Service Section (BLP). The data used were 60 respondents. Data collection was carried out using a questionnaire via Google Form, before testing the hypothesis with multiple regression analysis, testing the quality of the data and testing the classical assumptions were carried out first. The results of this study indicate that the accuracy of budget targets has a positive and significant effect on the performance accountability of government agencies